Employee Capability and Service Quality Linking Leadership to MSME Resilience in Small Hotels - Dasmadi; Sri Hartono; Muhammad Ghalih (Yayasan Ghalih Pelopor Pendidikan, 2026)
This study examines how entrepreneurial ecosystem and entrepreneurial leadership influence MSME resilience in the small hotel sector in Indonesia. Drawing on dynamic capability theory, the study proposes that resilience is achieved through the sequential mechanisms of dynamic capability and service quality. Data were collected from 262 owners and managers of small accommodation businesses and analyzed using PLS-SEM. The results indicate that both entrepreneurial ecosystem and entrepreneurial leadership significantly enhance dynamic capability, which in turn improves service quality and ultimately strengthens MSME resilience. The findings further reveal that service quality plays a critical role in translating internal capabilities into sustainable outcomes. This study contributes to the literature by offering a process-based explanation of MSME resilience and highlighting the importance of capability development and service delivery in service-oriented industries. Practical implications are provided for MSME development and tourism policy.